HELICOBACTER PYLORI INFECTION IN CHILDREN PRESENTING WITH RECURRENT ABDOMINAL PAIN: H- Pylori Infection in Children - Punhal, Muhammad; Malik, Qudratullah; Iqbal, Amjad (Pakistan Armed Forces Medical Journal, 2016)
Objective: To determine the frequency of Helicobacter Pylori (H. pylori) infection in children presenting with recurrent abdominal pain (RAP).Study Design: Descriptive cross-sectional study.Place and Duration of Study: This study was conducted at Combined Military Hospital (CMH) Quetta over a period of 10 months from 01-08-2011 to 31-05-2012.Material and Methods: A total of 83 children with recurrent abdominal pain were included in this study. Blood samples of patients were analyzed in laboratory of CMH Quetta for H. pylori Antibody (Ab) titers.Results: Mean age of the patients was 8.12±3.46 years. Distribution of gender showed that 44 patients (53.1 %) were male while 39 patients (46.9 %) were female. Mean duration of symptoms was 15.8%±3.7 months. H. pylori infection was present in 27 (32.5%) patients. Topical ciprofloxacin is more effective in earlier control of congestion and discharge of ear in CSOM; (p value